Effects of Green Brand Positioning, Knowledge and Attitude on Green Product Purchase Intention - Ai Chin, Thoo; Haslinda Binti Mohd Lawi, Nor; Merlind Muharam, Farrah; Haiyat Abdul Kohar, Umar; Liat Choon, Tan; Zakuan, Norhayati (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, customers are more conscious of environmental problems and have started to purchase green products. This study aims to evaluate the impacts of green brand positioning, green brand knowledge and attitude towards green brand on green product purchase intention. Data were collected from 162 respondents in Johor using snowball sampling technique and online survey. The data were analysed using the Statistical Package for the Social Sciences (SPSS). Multiple regression was used to test the relationships between green brand positioning, green brand knowledge, attitude towards green brand and green product purchase intention. The results show that the green brand positioning and green brand knowledge have significant and positive relationship between green product purchase intention. The study found that green consumer knowledge is the strongest predictor in green product purchase. However, consumers’ attitude toward green brand is not related to green product purchase intention. The findings of the study are important to green marketers to provide high availability of access to increase the demand of green products. Also, green marketers should emphasise on quality, price and advertisement in order to increase the demand of green products.